Comparison of Microstructure and Properties of Co119 Alloy Coating Prepared byOxyacetylene Surfacing and Induction Cladding - SHI Hai-fang, WANG Hong-lei (Cailiao Baohu)
In order to improve the environmental conditions during the bit conesand jaws’ production and the performance of the wear-resistant coating on the thrust surface, induction cladding could be used to replace the traditionally produced oxyacetylene surfacing to prepare the wear-resistant coating to increase the service life of roller cone bits. However, there are few such studies presently. Using HR-BP-120 induction heating equipment, HRC-150 Rockwell hardness tester, inverted microscope, and ML-10 abrasive wear testing machine, hardness, microstructure and wear resistance of the two coatings were compared. Result showed that compared with oxyacetylene surfacing, alloy coatings with the same composition prepared by induction cladding could also make fully metallurgical bonding. On this basis, the hardness value fluctuated less, which was 3.8 HRC higher than that of oxyacetylene surfacing, up to 61.8 HRC. Also, the microstructure was more fine and uniform, and the wear resistance was improved by 28.8%. Meanwhile, the method of induction cladding was cleaner.